Several Dynamic Properties of Solutions to a Generalized Camassa-Holm Equation - Zheng Yin (Abstract and Applied Analysis, 2013)
For a nonlinear generalization of the Camassa-Holm equation, we investigate the dynamic properties of solutions for the equation under the assumption that the initial value u0(x) lies in the space H1(R). A one-sided upper bound estimate on the first-order spatial derivative, Lp bound estimate, and a space-time higher-norm estimate for the solutions are obtained.